If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) = 2(x + 2) + 4x Reorder the terms: 6(-2 + x) = 2(x + 2) + 4x (-2 * 6 + x * 6) = 2(x + 2) + 4x (-12 + 6x) = 2(x + 2) + 4x Reorder the terms: -12 + 6x = 2(2 + x) + 4x -12 + 6x = (2 * 2 + x * 2) + 4x -12 + 6x = (4 + 2x) + 4x Combine like terms: 2x + 4x = 6x -12 + 6x = 4 + 6x Add '-6x' to each side of the equation. -12 + 6x + -6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 -12 + 0 = 4 + 6x + -6x -12 = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 -12 = 4 + 0 -12 = 4 Solving -12 = 4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 14x^2-9x+1= | | 48+4y-17=12y-11-2y | | 8x+12=47 | | 3(log)4x+9=10 | | 1.25x+6=1.95x+2 | | -7x+15=8 | | -6n(5+8n)=-366 | | X^2+2x*1=0 | | 13=8+5t | | -7(t)=10t-19 | | 15+3x-15= | | 3log(4x+9)=10 | | 5x=20(x-2) | | 5x-10+10x=-6 | | 6x+4=x-4 | | 5x^2+6+1= | | 300=4.9t^2 | | 8x+24-2x=0 | | 180=x+x*3 | | 2x+12-8x=17-19x+13x-5 | | (x-9)*x=36 | | X-9*x=36 | | 5y+90=6x | | 5x+4y-3(5x-2y)= | | gs+5=16 | | 6[n-4]=3n | | 6+1x=3 | | 7+6(-6a+7)=-167 | | (2x+7)(5x+2)(x-4)=180 | | 8-2x=-1 | | 7d^4=35d^3 | | 6(7a+4)-4a=100 |